Privacy issues in social networks and analysis: a comprehensive survey. Issue 2 (1st March 2018) - Pham, Vu Viet Hoang; Yu, Shui; Sood, Keshav; Cui, Lei
Abstract : Social networks have become part of today's life; however, they also create numerous privacy problems for their users as they reveal sensitive information. Thus, the privacy preservation has become a big problem in social networks and there are several researches related to this topic. However, the current research achievements for this issue are only ad hoc solutions and the broad picture of the problem is not clear. This paper surveys a wide range of related researches and realises that the topic includes many sub‐areas; for example, the privacy in publishing social network data for the use of third‐party consumers or the privacy of users in the leakage of individuals' information to unexpected people in their social circle. The study also analyses the advantages as well as limitations of proposed solutions. On the basis of that the research outlines key outstanding issues and recommends directions for the future research. Moreover, the research also investigates common privacy metrics and popular privacy‐preserving techniques to provide readers some basic tools to resolve open problems in the topic. The ultimate purpose of this research is to pave a solid background for people, who are interested in the topic, to do research further.